2015
DOI: 10.1016/j.molcel.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Massively Systematic Transcript End Readout, “MASTER”: Transcription Start Site Selection, Transcriptional Slippage, and Transcript Yields

Abstract: SUMMARY We report the development of a next-generation sequencing-based technology that entails construction of a DNA library comprising up to at least 47 (~16,000) bar-coded sequences, production of RNA transcripts, and analysis of transcript ends and transcript yields ("massively systematic transcript end readout," MASTER). Using MASTER, we define full inventories of transcription start sites ("TSSomes") of Escherichia coli RNA polymerase for initiation at a consensus core promoter in vitro and in vivo, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(138 citation statements)
references
References 26 publications
7
131
0
Order By: Relevance
“…In separate studies in which all possible DNA sequences between the -10 hexamer and the TSS were examined in vitro, as well as the distance between the leading edge and trailing edge of the promoter complex, it was concluded that TSS position correlates with scrunching state and is dependent on the absence of a σ 1.2 interaction with the discriminator (26,27). These data are consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 87%
“…In separate studies in which all possible DNA sequences between the -10 hexamer and the TSS were examined in vitro, as well as the distance between the leading edge and trailing edge of the promoter complex, it was concluded that TSS position correlates with scrunching state and is dependent on the absence of a σ 1.2 interaction with the discriminator (26,27). These data are consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 87%
“…To define the contribution of sequence-specific RNAP-G CRE interactions to TSS selection, we used a high-throughput sequencing-based methodology termed massively systematic transcript end readout (MASTER) (11). MASTER entails the construction of a template library that contains up to 4 10 (∼1,000,000) bar-coded sequences, production of RNA transcripts from the template library in vitro or in vivo, and analysis of transcript ends using highthroughput sequencing (11,13).…”
Section: Resultsmentioning
confidence: 99%
“…MASTER entails the construction of a template library that contains up to 4 10 (∼1,000,000) bar-coded sequences, production of RNA transcripts from the template library in vitro or in vivo, and analysis of transcript ends using highthroughput sequencing (11,13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations